A feasibility study on the use of an MEFP as an area denial charge - Koivusalo, Lauri (My University, 2026)
This thesis explores the behaviour and performance of MEFP charges and proposes a novel solution for an integral type MEFP charge for use as an area denial charge for lightly armoured targets. This was done by conducting a literature review to document the current state of MEFP technology, figure out a baseline for the charge performance, and to study the various parameters affecting MEFP performance. Following the literature review was done, an EFP charge was designed and tested in Impetus Defense -simulation environment as well as with an experiment to validate the simulation results. Finally, an MEFP charge was designed and tested in the simulation environment. Both liner deformation as well as penetration capability were assessed. As a basis for this thesis, a technology gap was identified between traditional shaped charges with high penetration capability and fragmentation charges with the ability to produce a cloud of fragments to hit multiple points in the target. A hybrid solution was required for lightly armored targets which are not optimal for either shaped charges, or fragmentation charges. An MEFP charge was identified as a suitable technology suited for this application. The literature review concerns EFP charge design, as well as shaped charge simulations and penetration mechanisms. As liner design plays a large part in EFP design various aspects affecting liner deformation are studied. These include material choice, geometric parameters and charge parameters. Common liner deformation mechanisms are outlined. An important part of EFP performance is its penetration capability and BAD generation. Different penetration processes and material failure modes are explained. The various types of MEFP charges and their construction are explained. These processes can be studied with simulations based on a material damage model, calculated with a FE or a particle-based method. The most common damage model is the Johnson-Cook model which has been proved to produce reliable results. An EFP charge was designed with SolidWorks and simulated with Impetus Defense. After acceptable results in the simulation environment were achieved, a test charge was fabricated and tested to validate the results from the simulation. The charge liners were pressed from an OFHC -copper plate to form hexagon shaped arc liners. The charge shell was fabricated with additive manufacturing filled with explosive material similar to the simulation. Initiation was done with a commercially available detonator. In the simulation environment, initially a single liner EFP charge was tested. A projectile much like the examples from the literature review was produced from the hexagonal liner. The projectile possessed a solid nose and a skirt with six fins. The EFP test charge produced results similar to the simulated charge and was able to penetrate 20 mm of RHA. Following the experiment, an MEFP charge was designed and simulated. The MEFP charge was able to produce seven projectiles with a velocity close to 1900 m/s and were able to penetrate over 18 mm of RHA. Further study on this subject is required. Controlling the detonation front shape and limiting the divergence and deformation of the peripheral liners in a liner array, needs further investigation. I want to thank Oy Forcit Ab and my thesis supervisors for providing all the necessary facilities and resources for conducting this thesis and for the vastly interesting thesis topic.
Keywords: MEFP; explosively formed penetrator; shaped charge; CAD; simulation; penetration; fragmentation